Efektifitas Model Pembelajaran dan Self-Efficacy Terhadap Hasil Belajar Senam Lantai Peserta Didik SMP - Muliartini, Ni Nyoman; Artanayasa, I Wayan; Danardani, Wasti; Sudiana, I Ketut; Semarayasa, I Ketut (Jurnal Sporta Saintika, 2024)
This research aims to determine the role of the NHT type cooperative learning model and the PBL learning model on floor exercise learning outcomes for students who have low self-efficacy. This type of research is quasi-experimental research. The population of this research was class VII students at SMP Negeri 1 Manggis, totaling 246 people. The total sample in this study was 80 students selected using a simple cluster random sampling technique. The data collected in this research is in the form of floor exercise learning results. Data on floor exercise learning outcomes were collected using a floor exercise skills test. Data analysis was carried out using inferential and two-way ANOVA tests followed by the Least Significant Difference (LSD) test. The research results show that the NHT type cooperative learning model is more effective than the PBL learning model for students who have low self-efficacy (F=4.282, p<0.05).